PENGARUH LIKUIDITAS DAN DEPOSITO TERHADAP PEROLEHAN LABA PERUSAHAAN PADA PT. BANK NEGARA INDONESIA (PERSERO), Tbk. KCP KOLAKA - Rusdiah Hasanuddin (Universitas Andi Djemma, 2024)
This research aims to determine the influence of liquidity and the influence of deposits on the company's profit at PT Bank Negara Indonesia (Persero) Tbk KCP Kolaka. The method used is quantitative descriptive, which seeks to explain and examine how an independent variable influences the dependent variable. The data used is secondary data in the form of Financial Reports which have been processed in 2017 - 2021 at PT Bank Negara Indonesia (Persero) Tbk KCP Kolaka. The analysis method used is multiple regression analysis. The research results show that 1) Liquidity partially has a significant effect on company profits at Banak Negara Indonesia (Persero) Tbk, Cab Kolakawhich is smaller than 0,005 2) Deposits partially have a significant effect on company profits at Bank Negara Indonesia (Persero) Tbk which is smaller than 0,005